PROTEOME PROFILING OF RBC MEMBRANE FROM SICKLE CELL ANAEMIA PATIENTS USING SPOTPAIR, A USER FRIENDLY TOOL FOR VIRTUAL PAIRING OF PROTEIN SPOTS FROM DIFFERENT 2D GEL ELECTROPHORESIS. - DIVYA SUDHIR TYAGI; JAGANNATH PAL; MONA CHOUBEY; PRAFULL KUMAR KHODIAR; PRADEEP KUMAR PATRA (International Journal of Pharma and Bio Sciences, 2016)
Sickle cell disease (SCD) is a hemolytic disorder caused by mutation in beta-globin gene and affects millions of people worldwide. Red blood cells (RBC) from patients with sickle cell anemia reveal a large array of membrane abnormalities which is associated with protein-protein interaction. In this work, a proteomic approach is adopted to resolve the differentially regulated proteins of erythrocyte membrane. Present work was carried out in the SCD patients of Chhattisgarh. The aim of this study was to analyse the expression of RBC membrane and to use it as biomarker. For present study 20 HbSS blood samples were taken after taking informed patient consent and compared with HbAA using 2 Dimensional gel electrophoresis (2D-DIGE) and by mass spectroscopy, analysis of 2D-DIGE was made using software SPOT pair. In present study, we found 32 proteins with altered expression out of which 12 were over expressed and 20 were under expressed. SPOT pair is platform independent software based in linear search technique Software is designed to figure out the position of same protein and its comparison in terms of their expression (under expressed or over expressed), further conformation in any changes in proteins can only be made by mass-spectrometric analysis. We propose this method (SPOT pair) to make 2-D PAGE analysis more apparent than the pre-existing methods like protpair.